If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 53 = 9x + -13 Reorder the terms: 53 + 6x = 9x + -13 Reorder the terms: 53 + 6x = -13 + 9x Solving 53 + 6x = -13 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 53 + 6x + -9x = -13 + 9x + -9x Combine like terms: 6x + -9x = -3x 53 + -3x = -13 + 9x + -9x Combine like terms: 9x + -9x = 0 53 + -3x = -13 + 0 53 + -3x = -13 Add '-53' to each side of the equation. 53 + -53 + -3x = -13 + -53 Combine like terms: 53 + -53 = 0 0 + -3x = -13 + -53 -3x = -13 + -53 Combine like terms: -13 + -53 = -66 -3x = -66 Divide each side by '-3'. x = 22 Simplifying x = 22
| x/4=x/5+7/4 | | 7(x)+3(x)+90=180 | | 16+8z-16=7z+5 | | y-9+4x+13+y=180 | | 72=2x+16 | | -16n+10=-14n-6 | | 2(x)+2(x)+x=180 | | 2y+4x=176 | | 8-9x=133-44x | | 456=2y+23 | | 55=6x+16 | | (20+4x)/(4+2x) | | 12=2m+4 | | x^2+x-30=y | | 3/5x+4=17 | | x/5-3.2=-15.7 | | x(x-1)=20 | | 8x-4[4-(-7-5x)]= | | 6x-2=13x+79 | | 60=11x-6 | | 142=230-y | | 4x+24=11x-6 | | 3.9x-11.2=4.6 | | 5x-2[6-(8-4x)]= | | 78=6x+24 | | 60=x+69 | | 3.9-11.2=4.6 | | 3-4x/3 | | 2x-6/5 | | (2/3)x=18 | | 8x-3[2-(4-4x)]= | | 4.38-3.9=14.544+1.2c |